Exception to the Rule: Genomic Characterization of Naturally Occurring Unusual Vibrio cholerae Strains with a Single Chromosome - Gary Xie; Shannon L. Johnson; Karen W. Davenport; Mathumathi Rajavel; Torsten Waldminghaus; John C. Detter; Patrick S. Chain; Shanmuga Sozhamannan (International Journal of Genomics)
The genetic make-up of most bacteria is encoded in a single chromosome while about 10% have more than one chromosome. Among these, Vibrio cholerae, with two chromosomes, has served as a model system to study various aspects of chromosome maintenance, mainly replication, and faithful partitioning of multipartite genomes. Here, we describe the genomic characterization of strains that are an exception to the two chromosome rules: naturally occurring single-chromosome V. cholerae. Whole genome sequence analyses of NSCV1 and NSCV2 (natural single-chromosome vibrio) revealed that the Chr1 and Chr2 fusion junctions contain prophages, IS elements, and direct repeats, in addition to large-scale chromosomal rearrangements such as inversions, insertions, and long tandem repeats elsewhere in the chromosome compared to prototypical two chromosome V. cholerae genomes. Many of the known cholera virulence factors are absent. The two origins of replication and associated genes are generally intact with synonymous mutations in some genes, as are recA and mismatch repair (MMR) genes dam, mutH, and mutL; MutS function is probably impaired in NSCV2. These strains are ideal tools for studying mechanistic aspects of maintenance of chromosomes with multiple origins and other rearrangements and the biological, functional, and evolutionary significance of multipartite genome architecture in general.